Estimation of extra-pancreatic necrosis volume and its correlation with the clinical outcome in acute pancreatitis - Thapa, Manish; Sharma, Pankaj; Ram, Birma (International Journal of Research in Medical Sciences, 2022)
Background: The aim of study was to measure extra-pancreatic necrosis volume in acute pancreatitis and associate with the clinical outcome and to determine the threshold volume of extra-pancreatic necrosis that predicts severity of acute pancreatitis. Methods: Hospital based observational study was carried out in the department of radiodiagnosis, Armed forces medical college, Pune, Maharashtra. All cases referred for CT scan in suspected cases of acute pancreatitis (by clinical and/or biochemical parameters) as a part of institutional protocol were included in the study. Multiplanar reconstruction with volumetric analysis was done for measuring the extra-pancreatic necrosis volume (EPNV) using inherent CT scanner volume assessing software. Results: Out of total 41 patients studied, more than one cause was identified in 9 patients. The most common cause of acute pancreatitis was alcohol use 32 (64%), followed by gallstone and diabetes mellitus (8% each). There was a positive correlation between EPNV and duration of hospitalization which was statistically significant with Spearman's correlation coefficient of 0.579 and p<0.001. Conclusions: Our study showed highly significant correlation between the EPNV and the prediction of end organ failure, systemic infection, duration of hospital stay and need for intervention. Statistically patient presenting with EPNV of more than 100 ml was closely associated with end organ failure; hence EPNV may be used as a useful scoring system. This study has highlighted the convenient and easier technique of predicting clinical outcome in patient by simply assessing the severity of acute pancreatitis by measuring EPNV.